Minimizing Group Index Variations in a Multicore Endoscope Fiber - Roper,JC; Yerolatsitis,S; Birks,TA; Mangan,BJ; Dunsby,C; French,PMW; Knight,JC (IEEE Photonics Technology Letters, 2015)
We describe a multicore fiber for nonlinear endoscopy where an ultrashort pulse is divided up and delivered through multiple cores to reduce the peak power. The variation in group index between cores of the fiber is minimized to allow simultaneously launched sub-pulses to arrive at the distal end of the fiber synchronously. Minimization of group index variation between cores is achieved at a V parameter of 3 owing to a turning point in the relationship between the group index and V parameter. For synchronized arrival times, single-mode propagation is important. By tapering a short length of the fiber at the launch end, the V value is locally brought below 2.405 allowing a pure fundamental mode to be launched into each core.